Maria Vodă Căpușan exégète de Mircea Eliade et du mythe théâtral - CĂPUȘAN, Horia (Studia Universitatis Babeș-Bolyai Dramatica, 2020)
Maria Vodă Căpușan as an Interpreter of Mircea Eliade and of the Theatrical Myth. The paper presents the contributions of Maria Vodă Căpușan in establishing the relationship between theatre and the other works of Mircea Eliade. The author underlines the importance of theatre which is seen not only as a minor preoccupation of an author famous for his contributions in the philosophy of religions, but also as an important part of her work being recognized in other domains. The author reaches the conclusion that without theatre we cannot understand the profound structure of the whole vision of Mircea Eliade.